Ability of the Digene Hybrid Capture II Test To Identify Chlamydia trachomatis and Neisseria gonorrhoeae in Cervical Specimens - Schachter, Julius (American Society for Microbiology, 1999)
The Digene Hybrid Capture II (HCII CT/GC) test is a combination test designed to detect Chlamydia trachomatis and Neisseria gonorrhoeae in a single specimen. It is a nucleic acid hybridization test which uses signal amplification to increase sensitivity. We compared its performance to that of culture on cervical specimens from 1,370 women. Direct fluorescent-antibody assay was used to resolve discrepant results for C. trachomatis. Samples were collected with a proprietary cervical brush or with endocervical swabs. The HCII CT/GC test proved to be sensitive and specific in detecting these organisms. Compared to N. gonorrhoeae culture, it had a sensitivity of 93% (87/94) and a specificity of 98.5% (1,244/1,263). Compared to C. trachomatis culture, the sensitivity was 97.7% (129/132) and specificity was 98.2% (1,216/1,238). Testing of some specimens with discrepant results by PCR suggested that the test would actually prove to be even more specific if it were compared to a nucleic acid amplification test (NAAT). The sensitivity of C. trachomatis culture was somewhat less, at 88.6% (117/132). The endocervical brush appeared to be better than Dacron swabs for collecting specimens. The HCII CT/GC test offers an attractive format that allows simultaneous detection of C. trachomatis and N. gonorrhoeae with a single specimen. An initial positive result is followed by repeat tests with probes to identify chlamydiae or gonococci. This test is more sensitive than C. trachomatis culture and is at least as sensitive as culture for gonococci. It deserves further evaluation and comparison with NAATs and may well offer an attractive alternative for diagnosis and screening of these infections.